Maternal exposure to carbon monoxide in the first trimester (7-13+6 weeks) of pregnancy in the core Niger Delta - Abbey, Mkpe; S. C., Amadi; U. S., Ocheche; F. C. C., Wekere; B. O., Altraide; O. A., Oloyede; N. M., Inimgba; C. I., Akani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Irrespective of the fact that the Niger Delta was known for its environmental pollution, neither organized environmental assessment nor human biomonitoring, including that of carbon monoxide (CO) had been performed in the region. The aim of the study therefore was to establish the severity of maternal impact on exposure to CO in the first trimester of pregnancy by quantifying the exhaled CO concentrations (ECOC) and to assess the effect of maternal age, body mass index (BMI) and parity on the severity of the impact. Methods: The study was of cross-sectional design carried out at the Rivers State University Teaching Hospital (RSUTH) in Rivers State. 490 consecutive pregnant women in the first trimester were recruited from the antenatal clinic from January 2021 to January 2022. Gestational age was estimated with the aid of ultrasound scan. Demographic, social and obstetric characteristics were taken. Exhaled carbon monoxide concentration (ECOC) was measured with the aid of a smokerlyzer. Data was analyzed, using the statistical package for social sciences (SPSS) version 25.0 (Armonk, NY) software. Ethical approval was obtained from the RSUTH ethics committee. Results: The mean value of ECOC 3.25±2.51 ppm was more than that obtained in other studies. Out of the total 490 patients that were assessed, 335 (68.37%) had mild impact from CO exposure (ECOC=1-3 ppm), 129 (26.33%) – moderate impact (ECOC=4-6 ppm) and 26 (5.31%) had severe impact (ECOC=more than 6 ppm). Moderate and severe impacts were more prominent in women of age groups 25-39 years and the differences in various age groups were statistically significant [X2=20.671, p<0.036, 95% CI (0.032, 0.040)]. Patients with higher BMI were more likely to have moderate and severe impact than those with lower BMI- 6 (33.33%) and 4 (22.22%) out of the 18 patients with class III obesity had moderate and severe impacts respectively. The differences in the impact at various BMI were statistically significant [X2=20.671, p<0.001, 95% CI (0.001, 0.002)]. There was inverse relationship between parity and the severity of the impact and the differences in various parity groups were statistically significant [X2=10.580, p<0.012, 95% CI (0.101, 0.113)]. There was also a paradoxical finding of 3 smokers having only mild impact. Conclusions: The mean value of ECOC 3.25±2.51 ppm was more than that obtained in other studies in non-pregnant women. Mild, moderate and severe impact from maternal CO exposure were established with the moderate and severe impact more prominent at maternal ages of 25-39 years, at higher BMI and at lower parity.